Commentary: Neurotoxicity of Local Anesthetics—An Issue or a Scapegoat?. Issue 6 (November 1998) - Moore, Daniel C.; Thompson, Gale E.
Abstract : Background and Objectives: To evaluate the etiologies of cauda equina syndrome (CES) and transient radicular irritation (TRI) or transient neurologic symptoms (TNSs ) following hyperbaric spinal anesthesia. Methods: A review of recent (since 1991) and prior (since 1941) investigations regarding CES and TRI (TNSs ) was conducted. Results: Recent publications fail to recognize significant prior information regarding CES and TRI (TNSs ). Conclusions: Cauda equina syndrome is, in all probability, explainable. Further investigation to pinpoint the etiology of TRI (TNSs ) is needed.